2001
DOI: 10.1093/aje/153.12.1142
|View full text |Cite
|
Sign up to set email alerts
|

Serum Carotenoids and Breast Cancer

Abstract: The consumption of vegetables and fruit may protect against many types of cancer, but research evidence is not compelling for breast cancer. Carotenoids are pigments that are present in most plants and have known antioxidant properties. Blood concentrations of carotenoids have been proposed as integrated biochemical markers of vegetable, fruit, and synthetic supplements consumed. In a case-control study (270 cases, 270 controls) nested within a cohort in New York during 1985-1994, the carotenoids lutein, zeaxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(108 citation statements)
references
References 40 publications
3
102
2
1
Order By: Relevance
“…There are several prospective studies investigating the possible effect of b-cryptoxanthin (and other carotenoids) on risk of various cancers. Toniolo found that levels of b-cryptoxanthin and lutein in serum were linked with reduced risk of breast cancer in a dose dependent fashion [32] . Beta carotene, lycopene, b-cryptoxanthin, zeaxanthin and lutein are reduced in colorectal adenomas, suggesting that mucosal carotenoids could serve as biomarkers for predisposition to colorectal cancer [33] .…”
Section: Discussionmentioning
confidence: 99%
“…There are several prospective studies investigating the possible effect of b-cryptoxanthin (and other carotenoids) on risk of various cancers. Toniolo found that levels of b-cryptoxanthin and lutein in serum were linked with reduced risk of breast cancer in a dose dependent fashion [32] . Beta carotene, lycopene, b-cryptoxanthin, zeaxanthin and lutein are reduced in colorectal adenomas, suggesting that mucosal carotenoids could serve as biomarkers for predisposition to colorectal cancer [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the assocation with the 'western' diet (characterized by meat, fat, dairy and sweets) remains unconfirmed [17,18], a number of other factors are now consistently associated with the risk of breast cancer; carotenoids decrease the risk [19] as well as folate [20]. The risk of low folate intake is more increased in combination with alcoholic beverages [21].…”
Section: Alcohol and Dietmentioning
confidence: 99%
“…Since increased blood levels of carotenoids were shown to be protective towards BC risk [53,[59][60][61], several studies evaluated the presence and the possible antioxidant activity of NAF carotenoids. While it was demonstrated that NAF carotenoid levels and their transport from the blood into the breast microenvironment may be enhanced by lactation [37], no association between BC risk and levels of provitamin A, carotenoid and vitamin E was found [9].…”
Section: Role Of Nutrients In Nipple Aspirate Fluids: Effects On Breamentioning
confidence: 99%
“…Several prospective or cohort studies have reported an inverse Vitamins [11,25] provitamin A [9] vitamin E [9] retinol [10,11,25] association between breast cancer risk and serum/plasma carotenoids, including a-and b-carotenes and lutein [59,60]. Despite being a relatively minor component among total carotenoids, it is intriguing that lutein showed a significant inverse association [25].…”
Section: Role Of Nutrients In Nipple Aspirate Fluids: Effects On Breamentioning
confidence: 99%
See 1 more Smart Citation